Visualizador de imágenes médicas para el seguimiento de tumores cerebrales (2020)
Tumor monitoring consists of evaluating different clinical characteristics of a patient over time in order to identify the progression of the disease or the response to different treatments. Metabolic medical images provide insights into the evolution of the tumor and are used by medical personnel to assess the patient's progress. In this work we propose the evaluation of diffusion medical images through quantitative metrics of regions of interest and visualizations which allow the identification of change in behavior from one time to another through a web application. The developed application allows the user to import, visualize and transform medical images of different formats and to perform comparisons between images through statistics and visualizations of regions of interest. The tool was implemented and validated with medical personnel to identify the requirements and opportunities for improvement in terms of functionalities and user experience throughout the execution of the project.